Sustainable Development Diplomacy and Nepal’s Foreign Policy - Shrestha, Rajendra Bahadur (NCWA Annual Journal, 2023)
Sustainable development is one of the great challenges of our time. The unprecedented crisis that we cross today is a blunt reminder of the need for cooperation across borders, sectors, and generations. More than ever international assistance is needed to deal with the Covid-19 crisis and its economic and social impacts. The United Nations has been spearheading major diplomatic efforts: to define sustainable development agenda for the world focusing think globally and acting locally. Sustainable development diplomacy builds on but significantly advances the traditional understanding of diplomacy. This situation calls for a stronger approach toward aid assistance (i.e., development cooperation) and development diplomacy, particularly the cooperation between developed and developing countries. A new understanding is needed to make the fight against poverty sustainable. A systematic approach and a clear framework for cooperation, coordination, and management should be established for multilateral, regional, and bilateral engagements. It has been realized that coordinated diplomacy must be built around networks drawn from several government ministries as well as the private sector and civil society. With the changing global environment over the years, the United Nations has evolved and its importance for Nepal continues to remain even stronger. Both diplomats and practitioners in the field are crucial in making these changes, and they need a good knowledge of what development cooperation is and how it functions since their tasks may include the support to the formulation of policies and strategies, the mobilization and allocation of funds, and negotiation and monitoring of development interventions. This paper has been prepared based on desk studies, utilizing relevant publications and websites.